The Study of “Make Over” Advertisement on Instagram Caption: Persuasive Analysis - Sholikhatin, Sholikhatin (English Literature Study Program, 2023)
This study discusses the persuasive techniques used in advertising women's beauty products on Instagram social media. This study examines